Energy security of Ukraine in the context of its sustainable development - Inna Semenenko (Institute of Economic Research (IER), 2015)
Energy security is an important issue for Ukraine's sustainable development. The main goal of the article is to show the state of energy security of Ukraine, analyze its tendencies and challenges, reveal the impact of energy security on sustainable development of a country. The state of the energy security of Ukraine was analyzed with the help of data collection, processing and analysis. Data was taken from State Statistics Service of Ukraine, Ministry of Energetics and Coal Industry of Ukraine, other sources, and analyzed with the help of tools of statistics and economic analysis. Ukraine, being a developing country and experiencing war, political and economic crisis, struggles for energy security support. The present state of energy availability and consumption in the country influences its sustainable development and political stability, and is a significant restraint in country's survival. Despite the fact, that Ukraine has enough resources' deposits to provide itself with energy, it provides less than 50% of own demands and is dependent on Russia's resources. Production of energy in Ukraine is decreasing, but energy consumption remains high. Ukrainian industries are energywasteful and energy inefficient; the country has the leading positions in energy intensity of GDP. The article shows relation of energy sources and energy security of Ukraine to sustainable development, reveals dependency of Ukrainian energy security and indicates its main threats and ways out.
Keywords: F5; O20; Q01; Q4; Q5; 330; energy security; fuel and energy resources; sustainable development; energy efficiency; energy consumption